Merekonstruksi Pemaknaan Terkait Persembahan Menurut Perkspektif J.L.Ch Abineno Dalam Kehidupan Jemaat - S Dulmanan, Neisy Ch; Tumiwa, Evi S. E. (DELAHA: Journal of Theological Sciences, 2025)
This study aims to analyze and elaborate on the concept of offering according to theologian J.L. Ch. Abineno and its relevance in the GMIM Betania. Although offering is often understood as an act of giving material things, Abineno offers a deeper theological perspective, where offering is seen as a response of faith and an act of gratitude of the people based on the holy offering of Christ on the cross. The methodology used is a qualitative literature study with a theological-analytical approach to Abineno's works,. The results of the study show that Abineno distinguishes offerings into two main types: Sacrificium (Christ's perfect and once-for-all offering) and Oblatio (the offering of the people as a response of gratitude). Material offerings (money, possessions) are only one concrete manifestation of a more essential offering, namely the complete offering of oneself. This research aims to examine and analyze in-depth a digital theology-based pastoral care model as a response to pastoral challenges in the digital age. This approach goes beyond the use of technology as a mere tool, but rather integrates core theological principles—such as the theology of presence, theology of embodiment, and theology of community—with virtual tools and spaces. The methodology used is a qualitative literature study, analyzing key works by digital theologians such as Heidi A. Campbell and Tim Hutchings, and integrating these with pastoral practice.The results of this study demonstrate that effective digital pastoral care requires an understanding of technology as an environment, not just an instrument. This requires spiritual directors to "incarnate" in the digital space, establishing an authentic presence through platforms such as video calls, social media, and chat